Electodiposition kinetics, structure and optical properties of cadmium sulfide films - Klochko, N.P. (Functional Materials, 2007)
The selection of the optimal regimes for electrodeposition of near-stoichiometric cadmium sulfide (CdS) layers has been provided by means of voltammetric studies of cadmium and sulfur separate and joint electrodeposition kinetics in aqueous chloride solutions. Optical analysis has discovered that the deposited films were transparent, characterized by straight allowed optical transitions and band gap typical for cadmium sulfide. X-ray diffraction results have shown that these films consist mainly of hexagonal modification CdS nanocrystals.